Relationships between Financial Information Richness and Decision Making Efficiency of Real Estate Business in the Northeast of Thailand - Waluwanarak, Kanyawan; Tangpinyoputthikhu, Asst. Prof. Dr. Yanin; Posri, Asst. Prof. Dr. Witchuda (Journal for Developing the Social and Community, 2019)
This research examined to test the relationship between Financial Information Richness and Decision Making Efficiency of Real Estate Business in the Northeast of Thailand. The sampling group was 164 persons in supporting staff of Real Estate Business in the Northeast of Thailand. The tool in this research was the questionnaire. The data were analyzed by multiple correlation analysis, simple regression analysis and multiple regression analysis. The research results found that : According to the analyses of correlations and effects, the financial information richness on operating information was correlates and positively impacted on overall decision making efficiency, be aware of the timeliness, objective achievement, best of effectiveness, stakeholder acceptance. Therefore, Management of the accounting department of real estate business in the Northeast of Thailand should to pay more attention to the financial information richness and cover all aspects to optimize the decision that accurate, timely, maximizing effectiveness. It is recognized by the people involved. The result is a competitive advantage and can achieve the purpose of real estate to be sustainable in the long term.